2012
DOI: 10.1089/ham.2011.1073
|View full text |Cite
|
Sign up to set email alerts
|

Compromised White Matter Microstructural Integrity after Mountain Climbing: Evidence from Diffusion Tensor Imaging

Abstract: The aim of the present study was to investigate cerebral microstructural alterations after single short-term mountain climbing. Voxel-based morphometry (VBM) analysis of gray matter (GM) and white matter (WM) volumes and Tract-Based Spatial Statistics (TBSS) analysis of WM fractional anisotropy (FA) based on MRI images were carried out on 14 mountaineers before and after mountain climbing (6206 m). In addition, verbal and spatial 'two-back' tasks and serial reaction time task were also tested. No significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 44 publications
3
49
0
Order By: Relevance
“…intracellular space of glia cells. Furthermore, these data identify similar locations of altered white matter water mobility as those observed previously in individuals after prolonged sojourns to high altitude 8,17,18 and in individuals native to high altitude. 19 It should be mentioned that by directly calculating T 2 and mean diffusivity, we avoided any potential confusion that 'T 2 -shine through' can cause on raw diffusion-weighted images.…”
Section: Discussionsupporting
confidence: 85%
“…intracellular space of glia cells. Furthermore, these data identify similar locations of altered white matter water mobility as those observed previously in individuals after prolonged sojourns to high altitude 8,17,18 and in individuals native to high altitude. 19 It should be mentioned that by directly calculating T 2 and mean diffusivity, we avoided any potential confusion that 'T 2 -shine through' can cause on raw diffusion-weighted images.…”
Section: Discussionsupporting
confidence: 85%
“…Decreased FA values are associated with cytotoxic brain edema. Therefore, both vasogenic and cytotoxic brain edema might develop in hypoxic patients, which are consistent with the findings in populations that are exposed to high‐altitudes (Zhang et al., 2012a). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, technically, ADC values can be directly obtained from ADC maps. Hypoxic brains have been shown to have both cytotoxic edema and vasogenic edema (Bailey et al., 2009; Zhang et al., 2012a), and hypoxia‐related DTI studies usually report both FA and ADC values. However, a previous study only calculated a decrease in FA on DTI maps in patients with COPD (Zhang et al., 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that the corticospinal tract, as well as the corpus callosum (anterior and posterior body, splenium) (CC) are particularly susceptible to hypoxia (Zhang et al. 2012, 2013; Hunt et al. 2013).…”
Section: Introductionmentioning
confidence: 99%